BOARD DIVERSITY AND PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2025)
This study investigated the role of board diversity in the performance of deposit money banks in Nigeria, with a focus on gender diversity, board composition, and board expertise. The study was guided by six objectives, which examined the relationship between these diversity attributes and two measures of financial performance, which are return on equity (ROE) and return on assets (ROA). Anchored on agency theory, resource dependence theory, and stakeholder perspectives, the research emphasized the importance of board oversight, monitoring, and inclusiveness in reducing agency costs and improving governance quality. An ex-post facto research design was adopted, relying on secondary data from the annual reports of First Bank Plc and United Bank for Africa Plc covering 2015–2024. Panel data analysis involving descriptive statistics, correlation, and regression techniques was employed to establish the relationships among variables. The findings revealed that gender diversity moderately and positively influenced ROE while exerting a weak positive effect on ROA, implying that the presence of women on boards enriches decision-making but is not a sole driver of financial performance. Board composition was found to have a negative relationship with both ROE and ROA, suggesting that excessively large or unbalanced boards hinder efficiency and accountability. Conversely, board expertise diversity had strong positive associations with both performance measures, underscoring the importance of appointing directors with diverse professional backgrounds in finance, law, economics, and management. The study concludes that while gender diversity improves inclusiveness, board expertise diversity remains the most decisive factor in enhancing shareholder value and resource utilization, and it recommends competence-based board appointments and policies that promote balanced and inclusive governance structures.
Keywords: Board Diversity; Corporate Governance; Financial Performance; Independence